Molten Salt Synthesis of the Plate-Like ABi4Ti4O15 (A= Ba, and Pb) for Methylene Blue Removal via Phocatalysis Effect - Anton Prasetyo; Muhammad Lathif Al-Abror; Usman Ali Rouf; Erna Hastuti; Widiya Nur Safitri; Arie Hardian (Jurnal Kimia Valensi, 2026)
One of the promising technologies for the treatment of dye-containing wastewater is photocatalysis. Among the compounds reported to exhibit good photocatalytic activity are Aurivillius compounds with plate-like morphology. In this study, the plate-like ABi4Ti4O15 (A= Ba and Pb) compounds was synthesized using the molten salt method. Diffractogram confirmed that the target compounds BaBi4Ti4O15 and PbBi4Ti4O15 were successfully synthesized but still found the impurities compound. And also the differences in the type of A-site cation (Ba and Pb) also affect the local structure, meanwhile, the SEM image showed that the particle morphology of all samples is plate-like, however, the particle size obtained is not uniform and agglomerated. The plot tauc calculations showed that BaBi4Ti4O15 has a band gap energy of 3.28 eV (378 nm), while that of PbBi4Ti4O15 is 3.03 eV (409.19 nm). Differences in the type of A-site cation (Ba and Pb) affect the band gap energy of the four-layer Aurivillius compound ABi4Ti4O15. Then the lower band gap energy of PbBi₄Ti₄O₁₅ results in a higher degradation capability toward methylene blue compared to BaBi₄Ti₄O₁₅. It also related to higher reaction rate constant of PbBi4Ti4O15. In addition, the another factor also influences the yield of methylene blue degradation by PbBi4Ti4O15 is its higher adsorption ability.